DIASPORA BAHASA MADURA DALAM MASYARAKAT PANDHALUNGAN BONDOWOSO - Mohammad Hairul (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
The Pandhalungan community is a unique society. It is called special because the Pandhalungan community is a hybrid society due to the mixing of two dominant cultures, namely Madura and Java, at the same time. Based on exposure, Therefore, the language used in community interaction Pandhalungan like the Bondowoso community is essential and exciting to study further. It remembers the results of previous research stated that Most of the Pandhalungan community speak Madurese. So there needs to be a scientific study of the Madurese diaspora. Moreover, the Pandhalungan community is settled in' Horseshoe,' East Java which incidentally is the island of Java, not the island Madurai. It is necessary to examine the pattern Pandhalungan community interaction by using an anthropolinguistic approach. Thus, the focus of this study, namely: (1) Migration of the Madurese to Bondowoso, (2) the old language and the new language of the Bondowoso Community, and (3) Primordialism of the Madurese Ethnic Society in Bondowoso. Third The focus of the discussion uses anthropolinguistic studies (a study that combines the study of cultural science/anthropology and the study of linguistics/linguistics). Keywords: language diaspora, Pandhalungan community, study Anthropology